2015
DOI: 10.1093/ejcts/ezv058
|View full text |Cite
|
Sign up to set email alerts
|

Negative prognostic influence of micropapillary pattern in stage IA lung adenocarcinoma

Abstract: MPP has an effect on tumour malignancy and patients with tumours harbouring a higher ratio of MPP or papillary predominant subtypes have worse survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 25 publications
5
27
0
Order By: Relevance
“…recently reported the proportion of MPC‐positive tumours to be 14%, the population of their study was confined to clinical stage IA lung ADCs. Furthermore, lymph node metastasis was reported to be significantly more frequent in MPC‐positive tumours, which is similar to the findings reported here.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…recently reported the proportion of MPC‐positive tumours to be 14%, the population of their study was confined to clinical stage IA lung ADCs. Furthermore, lymph node metastasis was reported to be significantly more frequent in MPC‐positive tumours, which is similar to the findings reported here.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, our incidence of MPC does not indicate over‐representation. Although Tsubokawa et al . recently reported the proportion of MPC‐positive tumours to be 14%, the population of their study was confined to clinical stage IA lung ADCs.…”
Section: Discussionmentioning
confidence: 99%
“…Nitadori et al (14) investigated surgically resected cases of small lung adenocarcinomas (≤2 cm) and indicated that a micropapillary component ≥5% was associated with an increased risk of recurrence, compared with a micropapillary component <5%. Tsubokawa et al (15) found that in stage IA patients with papillary and acinar predominant tumors, a micropapillary component ≥5% of the entire tumor negatively influenced survival. However, there was no difference in the prognosis of patients with micropapillary-positive and negative tumors with lepidic or solid predominant patterns.…”
mentioning
confidence: 99%
“…On the basis of our and others' previous publications that demonstrated worse prognosis in patients with micropapillary (MIP) subtype tumors who had undergone limited resection compared with those who had undergone lobectomy [19, 21], we investigated the utility of mPS in this cohort of patients (Figure 4). Within each setting, patients with high mPS had significantly lower survival estimates ( P < 0.001).…”
Section: Resultsmentioning
confidence: 99%